Предмет: Алгебра, автор: saikonosutoka84

Помогитеееее, СРОЧНО!

Приложения:

Ответы

Автор ответа: MagdaSinger
1

Ответ:

(3+ \sqrt{ 2 }  )(3- \sqrt{ 2}  ) =3^{2} -(\sqrt{2} )^{2} =9-2=7\\ ( 4- \sqrt{ 3} ) ( 4+ \sqrt{ 3 } ) =  4^{2} -(\sqrt{3} )^{2}=16-3=13\\ ( \sqrt{ 5}  - \sqrt{ 3}  )( \sqrt{ 5}  + \sqrt{ 3}  ) =(\sqrt{5} )^{2}-(\sqrt{3} )^{2}=5-3=2\\ (  \sqrt{ 10}  + \sqrt{ 17})(  \sqrt{ 10}  - \sqrt{ 17} ) =  (\sqrt{10} )^{2}-(\sqrt{17} )^{2}=10-17=-7

Объяснение:

Похожие вопросы
Предмет: Русский язык, автор: Sashayfif